2019
DOI: 10.17159/2413-3221/2019/v47n1a487
|View full text |Cite
|
Sign up to set email alerts
|

Poultry farmers' perceptions of extension service delivery through input providers in Ogbomoso zone of Oyo State, Nigeria

Abstract: This study examined commercial poultry farmers' perceptions of extension services rendered through input providers in Ogbomoso Agricultural Zone of Oyo State. A multi-stage sampling procedure was used in selecting 99 commercial poultry farmers. Data were collected using a structured questionnaire and analysed with descriptive and inferential statistical tools. The results showed that the mean age of farmers was 43.0± 7.1 years; most farmers (74.4%) were male, while 28.9% were educated. Input providers rendered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Agro-dealers play a vital role in ensuring the availability and accessibility of these inputs to farmers (International Fertilizer Association [IFA], 2018). They provide extension services to farmers (Owoade & Akinwale, 2019;Owoade et al, 2022;Verma et al, 2019) and inform them about possible solutions developed from research work to their problems, such as choosing the right chemicals or hybrid seeds for their farmland (Isah et al, 2023). However, there are several challenges that agro-dealers face in effectively carrying out their duties.…”
Section: Introductionmentioning
confidence: 99%
“…Agro-dealers play a vital role in ensuring the availability and accessibility of these inputs to farmers (International Fertilizer Association [IFA], 2018). They provide extension services to farmers (Owoade & Akinwale, 2019;Owoade et al, 2022;Verma et al, 2019) and inform them about possible solutions developed from research work to their problems, such as choosing the right chemicals or hybrid seeds for their farmland (Isah et al, 2023). However, there are several challenges that agro-dealers face in effectively carrying out their duties.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore essential to strengthen the advisory role being performed by input dealers towards bridging the shortage of public agricultural extension services in the country. Owoade and Akinwale (2019) reported that poultry input dealers provide extension services to commercial poultry farmers in Ogbomoso Agricultural Zone of Oyo State in Nigeria. Input dealers are located close to farmers than Village Extension Agents (VEAs), so they sell inputs to farmers, provide advice on use and act as opinion leaders (Ganiger, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Farmers can reduce greenhouse gas emissions, increase carbon sequestration and maintain above and below ground carbon stocks at relatively low cost, while also improving food production and livelihoods (Owoade et al, 2020). Improved agricultural practices can reduce carbon emissions from soil erosion and disturbance, and capture carbon from the atmosphere to store long-term in soils (Owoade, 2020). Practices like cover cropping, applying crop residues, mulch, manuring, reduced tillage and rotational cropping with legumes increase organic matter in soil, while also increasing crop yields.…”
mentioning
confidence: 99%